ANALISIS KADAR TOTAL FLAVONOID, ALKALOID SAPONIN, DAN TANNIN EKSTRAK BIJI JAMBU BOL (Syzygium Malaccense L) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Devitria, Rosa; Elfia, Mega; Yesti, Yulia; Astuti Sari, Winda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Indonesia is one of the world's island nations with high biodiversity of flora and fauna. The country's strategic geographical position is one of the factors contributing to its rich biodiversity. The global agreements on the disclosure and sustainable utilization of biodiversity for human needs are increasingly prevalent. Guava is rich in fiber, calcium, phosphorus, vitamin A, thiamine, riboflavin, ascorbic acid, and niacin. Although there is no medical research yet, Guava is believed to help alleviate constipation, diabetes, cough, headaches, and inflammation of the respiratory mucosa. Meanwhile, its seeds, bark, and leaves possess dynamic properties and have effects on blood pressure and respiration. To determine the properties of compounds contained in guava seed extract. This research uses quantitative and qualitative methods. The results of this research show that guava seeds have total flavonoid levels of 1.4008%, saponins 9.3363%, tannins 1.2703%, and alkaloids 1.8490%. The conclusion is that guava seeds contain positive secondary metabolite compounds including flavonoids, alkaloids, tannins and saponins. Keywords: Guava seeds, secondary metabolite compounds